PENGARUH PERSEPSI WAJIB PAJAK ATAS INTEGRASI NIK MENJADI NPWP DAN SOSIALISASI UU HPP TERHADAP KEPATUHAN WAJIB PAJAK - Sanda, Ditha Aprilia; Siregar, Dina Khairuna; Idayu, Riyanthi (LP2M Universitas Bina Bangsa, 2025)
The Government of Indonesia has passed Law No. 7 in 2021 concerning the Harmonization of Tax Regulations (UU HPP) which contains seven rules for changes and adjustments to tax regulations. One of them is the integration of NIK into NPWP which is the government's effort to increase tax revenue. This study aims to determine the influence of taxpayers' perception of the integration of NIK into NPWP and the socialization of the HPP Law on the compliance of individual taxpayers registered at KPP Pratama Serang Barat. The research method used is a descriptive quantitative method. The data collection method was carried out by the survey method using a questionnaire. The results of this study show that there is an influence of taxpayers' perception of the integration of NIK into NPWP on the compliance of individual taxpayers and there is an influence of socialization of the HPP Law on the compliance of individual taxpayers. And simultaneously taxpayers' perception of the Integration of NIK into NPWP and the socialization of the HPP Law affect the compliance of individual taxpayers